Farmacología básica y clínica - Katzung, Bertram G.; Vanderah, Todd W. (McGraw-Hill's AccessMedicina., 2020)
This book represents nearly 40 years of providing the most up-to-date information available in the field. This edition reflects a significant expansion of large molecule drugs in the pharmacopoeia, with numerous new monoclonal antibodies and other "biologics" covered in various chapters. Although complex drugs are still outnumbered by small molecule drugs, they have provided important therapeutic advances, and they constitute a significant and growing fraction of the resources available for pharmacotherapy. The fifteenth edition continues with the extensive use of full-color illustrations and expanded coverage of transporters, pharmacogenomics, and new drugs of all kinds.Basic & Clinical Pharmacology is designed to provide a comprehensive, accredited, and easy-to-read pharmacology textbook for students of any of the health sciences.